The Richthofen case by Veja Magazine A semiotic analysis of a sincretic text - Moraes, Suany Oliveira (Laboratório Editorial FCL-UNESP, 2008)
The objective of this present paper is to analyse, by the semiotic French line, the two initial pages of the special article of Veja maganize about Suzane Von Richthofen, published on 12, April, 2006, including one Suzane´s photograph that represents one of the mainly strategies to get the attention of the reader. This paper will only focus some aspects of the plan of expression and the plan of content and its possible relations.